17β-Estradiol and natural progesterone for menopausal hormone therapy: REPLENISH phase 3 study design of a combination capsule and evidence review. Issue 1 (May 2015) - Mirkin, Sebastian; Amadio, Julia M.; Bernick, Brian A.; Pickar, James H.; Archer, David F.
Highlights No combination natural estradiol/progesterone capsule is FDA or EMA approved. REPLENISH studies a natural estradiol/progesterone capsule (TX-001HR). Various doses of TX-001HR are being evaluated for treating hot flushes. Safety outcomes differ among types of estrogens and among types of progestogens. TX-001HR may be a safer hormone therapy option vs existing hormone therapies.